Effect of lanthanum doping on the far-infrared emission property of vanadium–titanium slag ceramic. Issue 22 (28th February 2017) - Zhang, Kewei; Deng, Yi; Yang, Yuanyi; Liao, Yongkang; Wang, Bozhi; Gong, Bing; Yang, Weizhong
Abstract : In the present study, a series of far-infrared ceramics were successfully synthesized using vanadium–titanium slag solid waste and some ordinary minerals as main raw materials with lanthanum (La) as an additive. Abstract : In the present study, a series of far-infrared ceramics were successfully synthesized using vanadium–titanium slag solid waste and some ordinary minerals as main raw materials with lanthanum (La) as an additive. The phase composition and microstructure of the prepared samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM). Besides, the far-infrared emission and absorption properties of the ceramics were determined via Fourier transform infrared spectroscopy (FT-IR). The results indicated that the doped La 3+ could efficiently promote the transformation of Fe 2+ to Fe 3+, which decreased crystallite size and increased lattice strain in the orthopyroxene-like structure. When doped with 9 wt% La, the vibration absorption intensities of Si–O–Mg and Si–O–Fe in orthopyroxene's irregular polyhedron and inerratic octahedron sites were strongest, which consequently contributed to enhanced far-infrared emissivity in 8–14 μm wavebands, reaching as high as 0.927. Moreover, the product exhibited a high bending strength of 30.45 ± 0.54 MPa for the La-doped groups, satisfying the requirement of ISO 13006 standard (>18 MPa). These results indicated that our prepared La 3+ -doped vanadium–titanium slag ceramics hold great promise for practical infrared applications due to their high far-infrared emissivity and excellent physical performances.